Challenges in pressure ulcer prevention. Issue 3 (20th June 2013) - Dealey, Carol; Brindle, C. Tod; Black, Joyce; Alves, Paulo; Santamaria, Nick; Call, Evan; Clark, Michael
Abstract Although this article is a stand‐alone article, it sets the scene for later articles in this issue. Pressure ulcers are considered to be a largely preventable problem, and yet despite extensive training and the expenditure of a large amount of resources, they persist. This article reviews the current understanding of pressure ulcer aetiology: pressure, shear and microclimate. Individual risk factors for pressure ulceration also need to be understood in order to determine the level of risk of an individual. Such an assessment is essential to determine appropriate prevention strategies. The main prevention strategies in terms of reducing pressure and shear and managing microclimate are studied in this article. The problem of pressure ulceration related to medical devices is also considered as most of the standard prevention strategies are not effective in preventing this type of damage. Finally, the possibility of using dressings as an additional preventive strategy is raised along with the question: is there enough evidence to support their use?